1999
DOI: 10.1111/j.1600-0447.1999.tb10837.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of clozapine and urinary incontinence in Chinese in‐patients

Abstract: Clozapine-associated urinary incontinence may be persistent in some patients, and it should be cautiously monitored in every patient taking clozapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 6 publications
2
56
2
Order By: Relevance
“…There are also a number of relatively large studies that showed sexual dysfunction to be more frequent in people with schizophrenia compared to normal controls (133)(134)(135). Increased prevalence of incontinence in people with schizophrenia have also been reported (136,137). Population-based studies on prostate cancer consistently found reduced incidences in people with schizophrenia (57,58,(61)(62)(63)(64)68), please note again that the samples in the Danish studies partly overlapped (61,68).…”
Section: Diseases Of the Nervous System (15 170 Medline Hits)mentioning
confidence: 98%
“…There are also a number of relatively large studies that showed sexual dysfunction to be more frequent in people with schizophrenia compared to normal controls (133)(134)(135). Increased prevalence of incontinence in people with schizophrenia have also been reported (136,137). Population-based studies on prostate cancer consistently found reduced incidences in people with schizophrenia (57,58,(61)(62)(63)(64)68), please note again that the samples in the Danish studies partly overlapped (61,68).…”
Section: Diseases Of the Nervous System (15 170 Medline Hits)mentioning
confidence: 98%
“…Clozapine-induced sialorrhoea occurs at a rate of approximately 30%, although it varies from 10 to 80% in the literature [1]. Nocturnal enuresis is a less frequently reported side-effect and incidence varies from 0.23% [2] to 41% [3]. It is possible that the occurrence of sialorrhoea and enuresis contributes to poor medication compliance.…”
mentioning
confidence: 94%
“…[2] Nocturnal enuresis is a less commonly reported side effect with a reported frequency varying from as little as 0.23% to as high as 41%. [3,4] We wish to report here a case of schizophrenia along with harmful use of cannabis, who developed both sialorrhea and enuresis while on clozapine, and who showed improvement in both the symptoms after receiving trihexiphenidyl.…”
Section: Trihexyphenidyl (Benzhexol) In Clozapine-induced Nocturnal Ementioning
confidence: 99%